The Influence of Artificial Intelligence on the Human Potential Development: The Views of Orthodox Clergy and Parishioners - Vinichenko, Mikhail V.; Rybakova, Marina V.; Nikiporets-Takigawa, Galina Y.; Chulanova, Oхana L.; Ljapunova, Natalia V. V. (Cuestiones Políticas, 2020)
The article discusses the nature of the influence of artificial intelligence on the development of human potential from the point of view of the Orthodox clergy and their parishioners. Methodologically, surveys and statistics were used to find out the opinion of the study subjects. A common phenomenon in the study was a unique consolidated position of all categories of Orthodox respondents on the danger that artificial intelligence represents. Most Orthodox are concerned about the unpredictability of creating and using artificial intelligence, especially in a pandemic. The authors considered the position of clergy, parishioners with and without a church on the nature of artificial intelligence's influence on human potential, the threats and risks to humans that come from artificial intelligence. The main advantage of the work is the results obtained on the basis of the comparative analysis of the positions of different categories of orthodox respondents on the nature of the influence of artificial intelligence on the development of human potential. In conclusion, the results can be used to develop a categorical-conceptual apparatus, to systematize knowledge about the use of artificial intelligence in the social and spiritual spheres.